Study the distribution of Fungi and Bacteria in AL- Yusifia River– South of Baghdad City.: Study the distribution of Fungi and Bacteria in AL- Yusifia River– South of Baghdad City. (Iraqi Journal of Market Research and Consumer Protection, 2015)
Al-Yusifia river was assessed at three sampling stations with study period from Autumn 2010 to the end of Summer 2011. The present investigation was carried out on diversity of fungi and bacteria from Al-Yusifia river, Baghdad city. During the study, a total of 12 fungal genus and 6 bacterial genus were isolated during the year seasons. The dominant fungus at the three stations were Penicillium sp., then Rhizopus and Trichophyton   megninii while the dominant bacteria was Escherichia coli and Klebsiella sp.            The higher fungi that occurred in station-I and this may be due to unpolluted nature of water and less anthropogenic activities was encountered at this station. Station II and III there were less in number of fungi. This may due to the polluted nature of the water and increased anthropogenic activities at this station, the higher bacterial genus was observed in station- III then station II and station I.            The results showed increased of fungal and bacterial genus during Summer and Spring in compare with other seasons due to convienance of temperature.